Phase separation in iron chalcogenide superconductor Rb₀.₈₊xFe₁.₆₊ySe₂ as seen by Raman light scattering and band structure calculations - Pashkevich, Yu.; Gnezdilov, V.; Lemmens, P.; Shevtsova, T.; Gusev, A.; Lamonova, K.; Wulferding, D.; Gnatchenko, S.; Pomjakushina, E.; Conder, K. (Физика низких температур, 2016)
We report Raman light scattering in the phase separated superconducting single crystal Rb₀.₇₇Fe₁.₆₁Se₂ with Tc = 32 K over a wide temperature region 3–500 K. The observed phonon lines from the majority vacancy ordered Rb₂Fe₄Se₅ (245) antiferromagnetic phase with TN = 525 K demonstrate modest anomalies in the frequency, intensity and halfwidth at the superconductive phase transition. We identify phonon lines from the minority compressed RbδFe₂Se₂ (122) conductive phase. The superconducting gap with dx₂₋y₂ symmetry has been detected in our spectra. In the range 0–600 cm–¹ we observe a weak but highly polarized B₁g-type backgroundwhich becomes well-structured upon cooling. A possible magnetic or multiorbital origin of this background is discussed. We argue that the phase separation in M₀.₈₊xFe₁.₆₊ySe₂ is of pure magnetic origin. It occurs below the Néel temperature when the magnetic moment of iron reaches a critical value. We state that there is a spacer between the majority 245 and minority 122 phases. Using ab initio spin-polarized band structure calculations we demonstrate that the compressed vacancy ordered Rb₂Fe₄Se₅ phase can be conductive and therefore may serve as a protective interface spacer between the purely metallic RbδFe₂Se₂ phase and the insulating Rb₂Fe₄Se₅ phase providing percolative Josephson-junction like superconductivity all throughout of Rb₀.₈₊xFe₁.₆₊ySe₂. Our lattice dynamics calculations show significant differences in the phonon spectra of the conductive and insulating Rb₂Fe₄Se₅ phases.